(untitled) (Dhaka University Journal of Biological Sciences, 2015)
Occurrence of Vibrio parahaemolyticus in fishes and shellfishes of coastal regions of Bangladesh was investigated. Fish and shellfish samples were collected from three coastal areas, namely Kuakata, Chittagong and Cox’s Bazar. Thirty five V. parahaemolyticus strains were isolated from 33 finfish and 6 shellfish samples where all the isolates were tlh positive which was species specific gene and no isolate had possessed the virulence gene encoding tdh. Overall prevalence rate of V. parahaemolyticus in fish sample was 45.45%; having 18.75% from Kuakata, 22.22% from Chittagong and 62.5% from Cox’s Bazar. Fifty per cent shellfish were found to be positive for V. parahaemolyticus. Antibiotic susceptibility of the isolated strains was carried out against 11 antibiotics where the isolates were sensitive to the tested antibiotics except metronidazole (50 μg) and nalidixic acid (30 μg). Presence of this pathogenic organism in fish and shellfish could pose a serious threat to fish industry as well as human health hazard in Bangladesh. Dhaka Univ. J. Biol. Sci. 24(2): 121-129, 2015 (July)